MENSTIMULUS KETERAMPILAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL ENGKLEK DI KELOMPOK B TK ARMAWIYAH 1 - Rini Novianti Yusuf; Dede Nurul Qomariah; Siti Hamidah Hamidah (Universitas Pendidikan Indonesia (UPI), 2022)
Children's motoric skills developed from birth, so they need a continuous stimulated to support the child's growth and development. Traditional games are mentioned as one of the effective ways to stimulate the development of gross motoric skills in children. This study aims to explore how to stimulated children's gross motoric skills through the traditional engklek game. Descriptive research method with a qualitative approach is used in this study. The results showed that simple motion exercises, the directional patting method, the